2007
DOI: 10.1177/0142723707076568
|View full text |Cite
|
Sign up to set email alerts
|

Development of pragmatic language comprehension in Finnish-speaking children

Abstract: ???The final, definitive version of this article has been published in the Journal, First Language, 27 (3) , 2007, Copyright SAGE Publications Ltd at: http://fla.sagepub.com/ " DOI: 10.1177/0142723707076568 [Full text of this article is not available in the UHRA]This research explores the development of pragmatic comprehension within the framework of relevance theory. Participants were 210 typically developing Finnish children aged from 3 to 9 years. The children were asked questions targeting the pragmatic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 41 publications
10
45
0
5
Order By: Relevance
“…Previous studies have shown that the ability to answer questions that demand complex contextual processing, such as understanding implicit meanings, develops with age (Loukusa et al, 2007;Loukusa, Ryder, & Leinonen, 2008;. At around eight years of age children begin to pay greater attention to all of the available relevant cues, including paralinguistic aspects of communication, and they no longer focus substantially on propositional content (Bosco, Angeleri, Colle, Sacco, & Bara, 2013;Morton & Trehub, 2001).…”
Section: Development Of Social-pragmatic Comprehensionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the ability to answer questions that demand complex contextual processing, such as understanding implicit meanings, develops with age (Loukusa et al, 2007;Loukusa, Ryder, & Leinonen, 2008;. At around eight years of age children begin to pay greater attention to all of the available relevant cues, including paralinguistic aspects of communication, and they no longer focus substantially on propositional content (Bosco, Angeleri, Colle, Sacco, & Bara, 2013;Morton & Trehub, 2001).…”
Section: Development Of Social-pragmatic Comprehensionmentioning
confidence: 99%
“…At around eight years of age children begin to pay greater attention to all of the available relevant cues, including paralinguistic aspects of communication, and they no longer focus substantially on propositional content (Bosco, Angeleri, Colle, Sacco, & Bara, 2013;Morton & Trehub, 2001). An earlier study by Loukusa et al (2007) showed that at the age of seven children can connect different kinds of contextual information in order to infer the implicit meaning of an utterance. Nevertheless, even if young children cannot yet resolve the implicit meanings of contextually complex utterances, they can utilize contextual information when identifying the object of references from the context (Bezuidenhout & Sroda, 1998;Loukusa, et al, 2007; or interpreting simple indirect utterances (Bucciarelli, Colle, & Bara, 2003).…”
Section: Development Of Social-pragmatic Comprehensionmentioning
confidence: 99%
See 3 more Smart Citations